Increased Complication Rate Associated with Podiatric Surgery. Issue 1 (January 2022) - Hoch, Caroline P.; Scott, Daniel J.; Brinton, Daniel L.; Maldonado, Lizmarie; Gross, Christopher E.
Category: Other; Ankle; Bunion; Diabetes; Hindfoot; Midfoot/Forefoot Introduction/Purpose: Nationally, there has been an increase in the scope of practice between orthopaedic surgeons and podiatrists. However, there is a paucity of studies in the literature comparing outcomes between orthopaedic and podiatric surgeons in different areas of foot and ankle surgery. Methods: A retrospective analysis was conducted using 2016-2017 5% US national sample of the Medicare limited dataset (LDS). This included a total of 527 patients undergoing one of 14 CPT foot and ankle specific codes. Basic demographics, medical comorbidities, and 1-year post-surgical complications were reviewed. One-hundred and eighteen patients were operated on by a podiatrist versus 409 who were operated on by a physician. Mean age was 69. Common procedures included gastrocnemius recession (n=168), ankle fracture open reduction internal fixation (168), and Achilles tendon repair (72). Continuous variables were compared using Wilcoxon-Mann Whitney test and categorical variables with chi-squared test. In addition, a multivariable regression was performed, evaluating the impact of various factors on odds of complication. Results: Between cohorts, there were no statistically significant differences in demographics, Charlson Score, COPD, hypothyroidism, hypertension, or obesity. There was a higher rate of peripheral vascular disease in patients treated by a podiatrist versus a physician (8.5% vs. 2.4%; P=.0025). Univariate analysis showed complication rates were higher among podiatrist compared to physicians (29.7% vs. 18.8%; P=.0113). Specifically, there were high rates of complications for bunion correction (4.2% vs. 1.0%; P=.0160), diabetic wound infection (11.0% vs. 1.5%; P<0.0001), and plantar fascia release (7.6% vs. 0.1%; P=.0001). Multivariable logistic regression showed patients operated on by a podiatrist had 84.1% greater odds of suffering a complication than those operated on by a physician (OR: 1.84, 95% CI: 1.15-2.96). Conclusion: Surgical treatment of multiple types of foot and ankle conditions by orthopaedic surgeons was associated with lower complication rates when compared with podiatrists. The reasons for these differences are likely multifactorial, but warrants further investigation. Our findings have important implications for policymakers, as well as for large healthcare systems and patients when selecting a treating provider for surgical problems.